Energy and macronutrients intake in indoor sport team athletes: Systematic review - Castillo, M.; Lozano-Casanova, M.; Sospeda, I.; Norte, A.; Gutiérrez-Hervás, A.; Martínez-Sanz, J. M. (Nutrients, 2022)
Indoor team sports are characterized by matches that are shorter in duration and with frequent substitution (high-intensity intermittent). The main goal of teams is to best cover athletes` physiological demands, while meeting their dietary intake needs is critical. The aim of this study is to conduct a systematic review of the dietary intake of indoor team sports athletes and to analyze whether they comply with nutritional recommendations. A search of PubMed-MEDLINE, Web of Science, and Scopus databases from 2008 to July 2022 was conducted and 2727 documents were identified. The studies focused on adult professional or semi-professional volleyball, basketball, handball, or futsal athletes. Two independent researchers screened and extracted the data, with 20 documents included after they met the inclusion criteria. Most of the athletes, both men and women, did not meet the official recommendations based on under-consumption (energy and carbohydrates) or over-consumption (fats). In relation to protein, 28.6% of studies met the recommendations, with 50% of those who did not meet it being due to under-consumption. Although there are references on athletes` dietary intakes, there are no references considering sexes or types of sport. More adapted recommendations are needed in order to more precisely evaluate athletes` intake to know if they meet their real nutritional requirements.